2013
DOI: 10.1007/s40135-013-0023-3
|View full text |Cite
|
Sign up to set email alerts
|

Children with Developmental Disability and Visual Impairment: What Information Can an Ophthalmologist Provide to Family and School

Abstract: Improved technology has increased survival of infants with serious medical conditions in the US, as well as worldwide, at a cost of significant developmental disability and sensory deficits in many children. This has created a public health challenge and is stressful to families who are the primary caretakers of children with complex medical problems resulting in disabilities. Children with comorbidities such as developmental disability and visual impairment have more difficulty than children with normal devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In addition, Philip 49 reports the importance of providing an assessment report to teachers and therapists involved in the child’s care so that they can take account of the child’s processing difficulties and ensure optimal access to education. The importance of communicating results from assessments is also echoed by Lehman 103 and Hyvärinen et al 104 who recommend documenting accommodations that are medically necessary so that carers and educators can make suitable adjustments to the child’s activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Philip 49 reports the importance of providing an assessment report to teachers and therapists involved in the child’s care so that they can take account of the child’s processing difficulties and ensure optimal access to education. The importance of communicating results from assessments is also echoed by Lehman 103 and Hyvärinen et al 104 who recommend documenting accommodations that are medically necessary so that carers and educators can make suitable adjustments to the child’s activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…This type of practical information has been shown to be important to carers in everyday living 9. Since the introduction of the BVFB to clinical use in Bradford, parents and carers have commented on the improvement in feedback they receive regarding their child's vision.…”
Section: Discussionmentioning
confidence: 99%
“…Parents like to know how much their child can see, and use this to guide them in selection of suitable toys or stimulation equipment. It has been reported that the use of functional description to enhance the visual function assessment and provide child-specific information to the parents/carers is crucial in ensuring that the child achieves its potential 9 10…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that communication between parents and teachers was not optimal. Lehman [14] highlights the importance of good communication between stakeholders involved in the child's care and notes that specific advice, including adjustments to the child's environment and visual materials, should be well documented and made available to educators to allow incorporation into the child's Individual Educational Plan (IEP) [14]. This encourages a joined-up approach to the child's care and ensures visual difficulties are accounted for to maximise children's access to the curriculum.…”
Section: Vision Reportmentioning
confidence: 99%
“…Impaired academic performance has been associated with visual deficits, in both mainstream and special education settings [12] and correction of visual deficits has a positive impact on classroom behaviour [13]. It is therefore important that meaningful information on visual status and visual need is effectively translated and delivered to all stakeholders involved in a child's care, including educators [14].…”
Section: Introductionmentioning
confidence: 99%